EFEKTIVITAS SOAL-SOAL KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Agung Purwantoro; Ajeng Rahmawati (Hipotenusa Journal of Research Mathematics Education (HJRME), 2019)
UMathematics is a science that explains concepts ranging from abstract ones to clearly defined ones. This is because mathematics is not derived from observation, but from ideas, processes, and deductive proofs. Therefore, many thinking abilities can be developed while learning mathematics. There are two levels of ability to think mathematics, namely low-level mathematical thinking skills (low-level mathematics thinking skills) and high-level mathematics (high-level mathematical thinking skills). Low-level mathematical thinking skills are more oriented to routine questions, there is no further development for students' self-exploration. Meanwhile, on the students' higher order thinking skills to develop and explore knowledge. There are various kinds of high-level mathematical thinking skills, including analytical skills, problem solving, understanding mathematical concepts, rational thinking, creative thinking, critical thinking, and mathematical connections. These abilities are no longer only oriented to the results and values achieved by students, but how these students construct their knowledge, understand concepts, and even solve problems. High-level mathematical thinking skills have not been widely developed in schools, so students have not been able to think creatively to solve the math problems they face. Efforts to raise the motivation of class XI students at SMA Negeri 1 Natar South Lampung in learning mathematics have been carried out by teachers in their field of study with various kinds ways, such as providing opportunities for students to ask questions, and designing learning in the form of group discussions. The core objectives of learning mathematics in schools are: (1) students are able to use the mathematics they learn in everyday life and in learning other subjects, (2) students form a coherent, critical, logical, creative and attitude mindset. consistent, honest, objective, careful, disciplined. To test the hypothesis proposed in this study, the author uses the t-count formula between tt < t with a significant level of 5%, the value of t = 0.98 < t = 1.76 so that Ho 2 is accepted , then the study shows that the average ability of students in the initial test of mathematical ability before applying contextual practice questions is 61.51, this ability is classified as moderate. After practicing contextual questions, the ability of students' mathematics learning outcomes increased to 65.15, this ability was still classified as moderate, but there was an increase of 65.15 - 61-51 = 3.64. Although this increase is still relatively moderate, from the difference in the numbers it is shown that there is a clear and effective increase.